Electromagnetic Fields: A Novel Prophylaxis for Steroid-induced Osteonecrosis - Ishida, Masashi (Springer-Verlag, 2008)
Establishing a means to prevent osteonecrosis after corticosteroid administration is an important theme. We asked whether pulsed electromagnetic field stimulation, a noninvasive treatment, could prevent osteonecrosis. Ninety rabbits were divided into four treatment groups: (1) exposure of 10 hours per day to electromagnetic stimulation for 1 week, followed by injection of methylprednisolone (20 mg/kg), and exposure of 10 hours per day to electromagnetism for a further 4 weeks (n = 40); (2) methylprednisolone injection only (n = 40); (3) no treatment (n = 5); and (4) exposure of 10 hours per day to electromagnetism for 5 weeks (n = 5). After 5 weeks, we harvested and histologically examined femurs bilaterally. The frequency of osteonecrosis was lower in the steroid-electromagnetism group (15/40) than in the steroid-only group (26/40). No necrotic lesions were found in the two control groups. We observed no clear effects of electromagnetism on the number, location, extent, and repair of necrotic lesions and intramedullary fat cell size in affected rabbits. Pulsed electromagnetic field stimulation reportedly augments angiogenesis factors and dilates blood vessels; these effects may lower the frequency of osteonecrosis. Exposure to pulsed electromagnetic field stimulation before corticosteroid administration could be an effective means to reduce the risk of osteonecrosis.